Ethics and democratic school management within the neoliberal state (Research, Society and Development, 2021)
This article is the result of a bibliographical study that intends to analyze education in a democratic perspective in the context of the neoliberal state, aiming to reflect the ethics and organization of school management within this space. It analyzes, through a brief history, the struggles for the redemocratization of the country, which influenced the elaboration of the Federal Constitution of 1988, and also those that aimed to improve the educational environment, demanding changes to new practices in the treatment of educational relations. This study emphasizes the principle of democratic management of public education, contemplated in article 206, item VI, of the Federal Constitution of 1988, the expression in the form of the law, added in item VI, which delegated legislation to the education systems. complementary, a fact that led to much discussion on the part of the struggle movements in the education sector about this partial achievement. With the emergence of new educational organizations, which brought into discussion the democratic and pedagogical practice in Brazilian public schools, and even after the regulation of democratic management in schools, there was still a yearning for implementation of actions with more participation of society in the taking of decisions, requiring a school management, active, ethical and democratic, ensuring in fact a new educational posture.